Between Support and Interests: The Role of Pancasila Youth in the Transactional Politics of the Palembang Regional Election - Muhammad Farhad Putra Agung; Amaliatulwalidain; Isabella (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the role of Pemuda Pancasila as an interest group within the context of transactional politics in the 2024 Palembang mayoral and vice-mayoral election. The research focuses on how Pemuda Pancasila, as a mass-based organization with an extensive network, strategically contributed to the local political contest, particularly in supporting a specific candidate pair through patron-client dynamics. The study employs a descriptive qualitative method. Data were collected through direct observation, in-depth interviews with key figures of Pemuda Pancasila in Palembang, and documentation from both primary and secondary sources. This research uses interest group theory, focusing on non-associational and resource-based indicators to examine the organization's involvement in local political dynamics. The findings reveal that Pemuda Pancasila actively participated in the 2024 Palembang election by supporting the Ratu Dewa–Prima Salam candidate pair. This support was not solely based on material transactions but was also influenced by organizational loyalty, personal relationships, and internal cadre consolidation. Pancasila Youth mobilized supporters, built strategic alliances, and leveraged its structured organization to reinforce its political stance. Moreover, resources such as membership strength, structural networks, and organizational facilities played a crucial role in enhancing the group's bargaining power in the local political arena. In conclusion, Pemuda Pancasila played a strategic role as an interest group in the transactional politics of the 2024 Palembang mayoral election. This role was demonstrated through mobilization efforts, loyalty-based political support, and effective utilization of available resources. The phenomenon reflects how civil society organizations can become influential actors in local political contests, operating within a spectrum of democratic participation and political pragmatism.